Thermal performance analysis of ETFE-foil panels and spaces enclosed with ETFE-foil cushion envelope - Afrin, Sabrina (2017)
Ethylene-tetra-fluoro-ethylene (ETFE) is a synthetic fluoropolymer. In the form of ETFE-foil it is applied in building envelopes in a single layer or more commonly, as inflatable cushions composed of multiple layers. ETFE-foils are widely used as a lightweight building envelope where high translucency, low structural weight, and complex shape is essential. However, limited research in the field of thermal performance of ETFE-foil panels and spaces enclosed with it instigated this study. Therefore, this study investigated (I) the thermal behaviour of ETFE-foil materials and the thermal performance of spaces enclosed with ETFE cushion roofs, (II) used commercially available thermal simulation software to predict the thermal performance of spaces enclosed with ETFE cushion and glass roofs and compared this with actual monitored behaviour (III) identified strategies to improve the thermal performance of spaces enclosed with ETFE cushion roofs in current and projected climate scenarios; and finally (IV) proposed design recommendations of ETFE-foil panels/cushions as a building fabric components. Material properties were investigated in laboratory based experiments. Further data were collected from two custom built outdoor test-rigs equipped with single-, two- and three-layer ETFE-foil panels. Environmental data were collected from two case study buildings to evaluate the thermal performance of the spaces enclosed with ETFE-foil cushion roofs. In addition, building simulation was conducted using EDSL TAS version 9.3.3.b to further analyse the indoor thermal environment and compare with monitored behaviour. The study identified variable thermal-optical properties of ETFE foils caused by various percentages of fritted area and its pigment density. The results also identified that the thermal environment of the test-rigs was affected by the variations in the surface temperatures of ETFE-foils and the temperature of air volume between multiple ETFE-foils (in case of two and three layer panels) by convective and radiative heat transfer mechanisms. The results from the case study buildings identified that during hot summer days, indoor air temperature and temperature stratification was higher in the atrium space enclosed with three-layer ETFE-foil cushions compared to the space enclosed with two-layer ETFE-foil cushion covered with rain mesh. However, both of the spaces were overheated during the summer of 2015. To develop an accurate simulation model for ETFE cushion roofs, a novel approach of modelling was developed. The simulation model was validated and calibrated by comparing with measured data from test-rigs and case study buildings. A comparison of predicted results of the spaces enclosed with a multi-layer ETFE-foil cushion roof and a glass roof showed that the extent of overheating was high when spaces were enclosed with glass roofs. Among two-and three-layer ETFE-foil cushion and glass roofs, two-layer ETFE-foil cushions with 75% fritting and rain mesh effectively reduced air temperature and cooling load during the peak summer period. The findings of this study will enable designers to select and develop design strategies for applying ETFE-foils in building envelopes on the basis of thermal and optical requirements. The study also suggested to change the view of current design practice that only focused on current conditions; such as the use of ETFE-foils may require more adaptive approach to mitigate overheating problems in projected climate.